Proposals for the study of UNRUH (effect) radiation with the help of entangled photons produced in electron-photon collisions - Ispirian, K.A. (Вопросы атомной науки и техники, 2012)
We consider some experiments proposed after 2006, which can be carried out with the help of high energy electron and powerful laser or X-ray photon beams.